The Relationship Between Green Accounting, Environmental Performance and Environmental Costs and Profitability: A Scoping Review - Sulastri, Ranti; Mulyadi, JMV; Sailendra, Sailendra (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
This study aims to determine the relationship between Green Accounting, Environmental Performance, and Environmental Costs with Profitability as well as the development of research conducted by previous studies. The research method carried out in this study uses the Scoping review method, which is an ideal study method to determine the scope of the scope of a collection of literature on a particular topic. The scope review also provides a clear picture of the volume of literature and provides a broad and detailed overview of the researcher. Of the many benefits obtained by mining sector companies, do these companies think about the impacts caused such as environmental damage or have awareness of implementing green accounting in the company? In its regulation, the Ministry of Industry has encouraged all mining companies to protect the environment in the production process. Industrial law number 3 of 2014 regulates green industry by underlining that green industry prioritises the use of resources more efficiently and sustainably, so that industrial development can be harmonised with the preservation of environmental functions and can provide benefits to society in the future. The results of this study from the many studies conducted by previous researchers are still not enough to have an impact on the awareness of industrial business actors to protect the environment in company operations.